Deciphering lignocellulose deconstruction by the white rot fungus Irpex lacteus based on genomic and transcriptomic analyses - Xing Qin; Xiaoyun Su; Huiying Luo; Rui Ma; Bin Yao; Fuying Ma (Biotechnology for Biofuels, 2018)
Abstract Background Irpex lacteus is one of the most potent white rot fungi for biological pretreatment of lignocellulose for second biofuel production. To elucidate the underlying molecular mechanism involved in lignocellulose deconstruction, genomic and transcriptomic analyses were carried out for I. lacteus CD2 grown in submerged fermentation using ball-milled corn stover as the carbon source. Results Irpex lacteus CD2 efficiently decomposed 74.9% lignin, 86.3% cellulose, and 83.5% hemicellulose in corn stover within 9 days. Manganese peroxidases were rapidly induced, followed by accumulation of cellulase and hemicellulase. Genomic analysis revealed that I. lacteus CD2 possessed a complete set of lignocellulose-degrading enzyme system composed mainly of class II peroxidases, dye-decolorizing peroxidases, auxiliary enzymes, and 182 glycoside hydrolases. Comparative transcriptomic analysis substantiated the notion of a selection mode of degradation. These analyses also suggested that free radicals, derived either from MnP-organic acid interplay or from Fenton reaction involving Fe2+ and H2O2, could play an important role in lignocellulose degradation. Conclusions The selective strategy employed by I. lacteus CD2, in combination with low extracellular glycosidases cleaving plant cell wall polysaccharides into fermentable sugars, may account for high pretreatment efficiency of I. lacteus. Our study also hints the importance of free radicals for future designing of novel, robust lignocellulose-degrading enzyme cocktails.